Mimicry-Memorization Method: Elevating Arabic Speaking Skills with Visual Media - Hafsari , Siti; Wahyudin , Dedih; Atiatulwafiroh , Siti; Budiyanto, Cepi; Wiwaha, Rizzaldy Satria (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2024)
This research aims to explore the effectiveness of implementing the Mim-Mem (Mimicry-Memorization) Method with the support of visual media in enhancing Arabic speaking proficiency in a school environment. The Mim-Mem Method combines mimicry for better understanding and memorization for vocabulary reinforcement, while visual media is utilized as a clear representation of the learning material. The research methodology employed is classroom action research with students from grade XI A at SMP IT Sahabat Alam Pelabuhan Ratu Sukabumi as the subjects. Data were collected through observations, tests, and field notes over two research cycles. The results were analyzed to measure the improvement in students' speaking abilities. The research findings demonstrate a significant enhancement in students' speaking skills after applying the Mim-Mem Method with visual media. The average scores increased from 64 in the pre-test to 81 in the post-test, indicating the effectiveness of this method as a learning approach. The discussion involves in-depth analysis regarding the positive impact of the Mim-Mem Method with visual media on Arabic speaking skills among students. The novelty of this research lies in the innovative combination of methods with a visual approach, providing an effective solution to learning challenges. In conclusion, the implementation of the Mim-Mem Method with visual media makes a positive contribution to improving Arabic speaking skills among students at SMP IT Sahabat Alam Pelabuhan Ratu Sukabumi. Recommendations for future research could focus on further developing this method, including variations in teaching approaches and more specific adjustments to students' characteristics. Additionally, further studies could explore the effectiveness of this method in higher education contexts or different educational environments.